Short- and Long-Term Effect of Parkinson’s Disease Multimodal Complex Treatment - Konstantin G. Heimrich (MDPI AG, 2021)
Parkinson´s disease multimodal complex treatment (PD-MCT) is a multidisciplinary inpatient treatment option increasingly applied in Germany. However, data on its effectiveness are rare. Data were collected at the Department of Neurology of the University Hospital Jena, Germany. In 2019, 159 patients were admitted to our neurology ward for PD-MCT. Patients were followed for up to 12 months, and their data were retrospectively analyzed to assess the short- and long-term treatment effects. The treatment led to an improvement in motor function assessed by Movement Disorder Society sponsored revision of the unified Parkinson´s disease rating scale part III (MDS-UPDRS III) and motor performance (Tinetti test). Improvement of MDS-UPDRS III was associated with lower age, higher MDS-UPDRS III at admission, and less depression (assessed by Hospital Anxiety and Depression Scale and Beck-Depression Inventory II). One month after the hospital stay, 36.8% of the patients reported feeling better, while 32.6% reported feeling worse. If the patients were not depressed, they were more likely to have reported feeling better. PD-MCT is an effective inpatient treatment option. However, to improve patients’ satisfaction, screening and treatment for depression is essential. The effectiveness of different treatment durations has to be elucidated in further studies.